2017
DOI: 10.1111/1751-7915.12836
|View full text |Cite
|
Sign up to set email alerts
|

Biofloc technology application in aquaculture to support sustainable development goals

Abstract: SummaryBiofloc technology (BFT) application offers benefits in improving aquaculture production that could contribute to the achievement of sustainable development goals. This technology could result in higher productivity with less impact to the environment. Furthermore, biofloc systems may be developed and performed in integration with other food production, thus promoting productive integrated systems, aiming at producing more food and feed from the same area of land with fewer input. The biofloc technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
111
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(117 citation statements)
references
References 31 publications
2
111
0
4
Order By: Relevance
“…Biofloc technology (BFT) system can be an environmentally friendly strategy to establish a near to zero water exchange culture system while providing potentially consumable biomass to the cultured animal (Avnimelech, ; Bossier & Ekasari, ). This operates on the principle of increasing carbon to nitrogen ratios, through the addition of an exogenous carbon source that consequently stimulates natural heterotrophic bacterial growth in the system (De Schryver, Crab, Defoirdt, Boon, & Verstraete, ; Hargreaves, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofloc technology (BFT) system can be an environmentally friendly strategy to establish a near to zero water exchange culture system while providing potentially consumable biomass to the cultured animal (Avnimelech, ; Bossier & Ekasari, ). This operates on the principle of increasing carbon to nitrogen ratios, through the addition of an exogenous carbon source that consequently stimulates natural heterotrophic bacterial growth in the system (De Schryver, Crab, Defoirdt, Boon, & Verstraete, ; Hargreaves, ).…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria will then convert otherwise toxic nitrogenous metabolites into microbial biomass known as bioflocs (Avnimelech, ; Ebeling, Timmons, & Bisogni, ). Bioflocs consist of various organic materials such as bacteria, microalgae, uneaten food, and zooplankton, which can serve as a constant supply of additional nutrients for aquatic animals that are capable of collecting and consuming these small particles (Bossier & Ekasari, ; Emerenciano, Gaxiola, & Cuzon, ). The use of BFT has successfully improved the growth and feeding efficiencies in various aquatic species such as Pacific white shrimp Litopenaeus vannamei (Khanjani, Sajjadi, Alizadeh, & Sourinejad, ; Serra, Gaona, Furtado, Poersch, & Wasielesky, ), tilapia Oreochromis niloticus (Long, Yang, Li, Guan, & Wu, ), and the carps Cyprinus carpio and Hypophthalmichthys molitrix (Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The technology is based on waste nutrient recycling, particularly nitrogen into microbial biomass. This biomass can be used directly by filter feeding species such as tilapia, carp, catfish, marine shrimp and freshwater prawns (Bossier and Ekasar, 2017). On a dry matter basis, microbial biomass has been shown to contain 20-45% crude Rotating bio-contactor 200…”
Section: Biofloc Farming Systemsmentioning
confidence: 99%
“…Biofloc systems are environmentally friendly due to the fact that there is almost no release of nutrient rich drainage water to the environment. Most studies has showed BFT reduces pollution and water exchange, increases fish production and improves feed utilization efficiency in aquaculture (Avnimelech, ; Avnimelech & Kochba, ; Avnimelech, Troeger, & Reed, ; Bossier & Ekasari, ; Crab, Chielens, Wille, Bossier, & Verstraete, ; Luo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies on BFT in aquaculture have been reported, BFT is still in its infant stage, and the relevant research and application of flocculating strains in aquaculture water are quite limited (Bossier & Ekasari, 2017;Luo et al, 2016).…”
mentioning
confidence: 99%